Hubungan Tingkat Kepercayaan Diri Terhadap Keberhasilan Free Throw Siswa Ekstrakurikuler Bola Basket SMAN 2 Klari - Ridho Setianovan; Febi Kurniawan; Siswanto Siswanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
The formulation of the problem in this study is whether there is a positive and significant relationship between self-confidence and the free throw results of basketball extracurricular students at Senior High School 2 Klari. This study aims to determine the relationship between self-confidence and the results of the free throw basketball extracurricular students of Senior High School 2 Klari. This research method is quantitative with correlation type to find out a relationship using a questionnaire as an instrument. Sources of data in this study were students of basketball extracurricular Senior High School 2 Klari totaling 30. To retrieve data using google form. Because in this study a questionnaire or questionnaire as evidence of all activities carried out in the research took place. The results showed that there was a relationship between parental attention and student learning outcomes, this was indicated by a correlation coefficient of 0,410> r table 0,361 and a significance level of 0,000 <0,05 with a moderate level of relationship. The coefficient (r2) is 0,168, this shows that self-confidence affects 40,98% on basketball extracurricular student learning outcomes and is influenced by other indicators such as having self-concept, self-esteem / self-esteem, exercising self-control, self-control , build self-image / self-image, self-achievement, and others.